Conciliation Procedure in the Russian System of Protection of Civil Rights - E.V. Mikhailova (Психология и право, 2022)
The article is devoted to the study of the legal nature of judicial conciliation procedure as a means of legal protection. Russian legislation does not determine the place of conciliation procedures in the system of protection of rights and legitimate interests. Despite the active legislative activity on the introduction of various forms of reconciliation into law enforcement, for the most part they remain unclaimed by the society. Unlike all other forms of settlement of legal conflicts, judicial conciliation is regulated by the norms of procedural legislation, which makes it an institution of public law and a kind of state activity. But for its successful integration into the system of legal protection, theoretical development of this institution is necessary. The differences between judicial conciliation and other forms of settlement of legal conflicts are shown. The institute of judicial conciliation is proposed to be called “a surrogate of judicial proceedings”. It is also proposed to establish a special requirement for judicial conciliators: they must have a higher education in the field of psychological sciences.